The Impact of Active Empathetic Listening on an Introductory Communication Course. Issue 3 (3rd July 2021) - Bletscher, Caitlin G.; Lee, SuYeon
Abstract: Listening skills are essential to interpersonal relationships and successful work in teams. Despite its necessity, most communication curriculum in higher education does not target students' listening skills. This study examines the impact of infusing an Active Empathetic Listening (AEL) module into a large, introductory university communication course. One hundred and seventy-two students ( n = 172) from four courses (fall 2018–spring 2020) completed a self-reported questionnaire measuring AEL at three time points across the semester. Results showed that the module made statistically significant differences within all three AEL subscales of sensing, processing, and responding. Results suggest that long-term exposure to the active listening curriculum are required to make behavioral pattern changes to their listening habits. Researchers conclude with recommendations for communication educators, shedding light on how AEL skills can be developed among college students.